1981
DOI: 10.1093/nar/9.10.2335
|View full text |Cite
|
Sign up to set email alerts
|

Temperature mediated variation of DNA secondary structure in (A.T) clusters; evidence by use of the oligopeptide antibiotic netropsin as a structural probe

Abstract: The titration viscometric investigation of the multi-mode interaction of netropsin (Nt) with (A.T) clusters of NaDNA12 and NH4DNA10 has been extended to different temperatures. The position of two boundaries on the r-scale (r= [Nt]bound/[DNA-P]) with increasing temperature steadily (rI/II) or more abruptly (rO/I) shifts to lower values. For the most (A.T) rich Nt-binding sites of modes (O), (I) and (II) this observation suggests the existence of an equilibrium between different DNA secondary structures with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In particular while in B-DNA the major groove represented the potentialLy priviLedged region for eLectrophiLic attacks in G-C rich segments and the minor groove such a region in A-T rich segments, the major groove will manifestly be predominant in A-DNA independen-tLy of its composition. This situation may perhaps be responsible in part for the fact that the recently much explored oligopeptide antibiotics netropsin and distamycin A, which interact without intercalation with nucleic acids and bind preferentialLy to the minor groove of A-T rich regions of helical B-DNA, bind much Less, if at all, to A-DNA or to helical RNA (whose structure is similar to A-DNA) (22)(23)(24). Other, complementary reasons for this selectivity could be 1) the more negative values of the potentials at N3(A) and 02(T) in B-DNA than in A-DNA, these atoms being the ones utilized for hydrogen bonding with the amide hydrogens of the antibiotics and 2) the unsuitable arrangement of the anionic oxygens of the phosphates (pointing across the entrance to the major groove) in A-DNA: in B-DNA hydrogen bonds linking the positively charged propionamidine group(s) of the antibiotics with these oxygens stabilize the interaction.…”
Section: -5mentioning
confidence: 99%
“…In particular while in B-DNA the major groove represented the potentialLy priviLedged region for eLectrophiLic attacks in G-C rich segments and the minor groove such a region in A-T rich segments, the major groove will manifestly be predominant in A-DNA independen-tLy of its composition. This situation may perhaps be responsible in part for the fact that the recently much explored oligopeptide antibiotics netropsin and distamycin A, which interact without intercalation with nucleic acids and bind preferentialLy to the minor groove of A-T rich regions of helical B-DNA, bind much Less, if at all, to A-DNA or to helical RNA (whose structure is similar to A-DNA) (22)(23)(24). Other, complementary reasons for this selectivity could be 1) the more negative values of the potentials at N3(A) and 02(T) in B-DNA than in A-DNA, these atoms being the ones utilized for hydrogen bonding with the amide hydrogens of the antibiotics and 2) the unsuitable arrangement of the anionic oxygens of the phosphates (pointing across the entrance to the major groove) in A-DNA: in B-DNA hydrogen bonds linking the positively charged propionamidine group(s) of the antibiotics with these oxygens stabilize the interaction.…”
Section: -5mentioning
confidence: 99%
“…Hogan et al (1979) reported an apparent length increase of 14 A per bound distamycin based on transient electric dichroism measurements and a similar increase was obtained for netropsin (Dattagupta et al, 1980). Reinert observed substantial changes in the hydrodynamic properties of DNA upon binding netropsin and distamycin by titration viscometry (Reinert 1981(Reinert , 1993a(Reinert , 1993bReinert et d., 1979Reinert et d., , 1981. Bound DAPI increases the flow orientation of poly-(dA : dT) by a factor of 2 as judged by linear dichroism (Eriksson et al, 1993).…”
Section: Properties Of the M-formmentioning
confidence: 80%
“…This study's results were similar to Lin Shi et al who described that COS positively affects the colon length and body weight of mice under DSS-induced colitis 26 . A study showed that oral administration of chitosan also enhances the body weight in rats 27 and mice 28 .…”
Section: Discussionmentioning
confidence: 99%